'An attempt to tip the scales': music and embodied capital in an English secondary school. Issue 3 (3rd April 2019) - Pollard, Dominic; Alexander, Patrick
Abstract: This article explores class, capital, and aspiration to social mobility in an ethnographic study of an English secondary school. In particular, the article considers the school's musical instrument programme as a site for inculcating forms of capital, under the auspices of developing skills for upward social mobility. Bringing together Bourdieu's conceptions of schooling with theories of materiality and situated learning, we contend that this school succeeds in cultivating new forms of embodied capital among students through the development of communities of musical practice. However, a tension remains between emancipatory aims of the programme and the sanctioning and championing of certain forms of dominant cultural practice. The learning environment of the instrument programme highlights the complex and conflicted impact that schooling can have on the development of cultural capital and on reproducing disadvantage and difference.